Developing Financial Mechanisms for Long-Term Funding of Biodiversity Conservation - Larsen, Jeri (World Bank, Washington, DC, 2012)
On March 12, 1992, the Regional Environment Divisions and the Global Environment Facility Administration in the Environment Department sponsored a one-day workshop. Conservation professionals, financial and legal specialists, and Bank operational staff involved with biodiversity, particularly Global Environment Facility (GEF) projects, gathered to discuss trust funds, endowments, and foundations as a means of providing long-term, continuous funding for biodiversity conservation. Following this, another workshop focusing on trust fund design for GEF biodiversity projects was held on July 31, 1992. The paper previewed in this article outlines the main issues and operational lessons from both workshops. It is dividied into three subheadings. The first section deals with issues in setting up a long-term financial mechanism; the second section addresses special considerations for the GEF; and the third summarizes conclusions from both workshops.